Infrared thermography in the diagnosis of Achilles tendinitis. A randomized double-blind pilot clinical trial - Lopes-Martins, Rodrigo Alvaro Brandão; Luis Filipe Beloni , Luis Filipe; Santos, Maria Célia Galvão; Cadenas Bueno, Felícia; Lopes-Martins, Pedro Sardinha Leonardo; Naterstad, Ingvill Fjell; Bjordal, Jan Magnus; Ferreira, Carlos Renato; Souza Sá Filho, Alberto; Leonardo, Patrícia Sardinha (Manual Therapy, Posturology & Rehabilitation Journal, 2023)
Background: The Achilles tendon (AT) is the widest and most resistant of the osteoarticular system and has the greatest load-bearing capacity. It is involved in daily functioning and sports activities performance. Exposure to excessive stress on the calcaneus tendon (CT) can prevent an effective repair process and favor permanent injuries. Tendinopathy is a clinical syndrome resulting from disorientation of AT fibers, and inflammatory signs characteristic of tendinitis or tissue degeneration present in tendinosis can be found. The condition can manifest itself through functional changes accompanied by clinical signs such as crackling, tenderness, pain and edema. Infrared thermography is used to trace thermographic profiles, capable of detecting thermal changes related to pathologies. Objectives: The main goal of this study was to correlate AT region thermograms with clinical and functional characteristics in healthy individuals with CT pathology. Methods: The present work consists of a double-blind pilot randomized trial, of qualitative and quantitative nature. Individuals with TC tendinopathy, classified in the Tendinopathy Group (TG) and individuals without tendinopathy, classified in the Control Group (CG) participated. Assessments were performed to characterize the subjects belonging to the TG and CG: anamnesis, infrared thermography, referred pain, crepitation and thickness on palpation, algometry, arch sign test and Royal London Hospital test, pain on passive dorsiflexion, pain on lifting the heel and long jump. Results: The results obtained in infrared thermography were consistent with those obtained in the clinical evaluation for TG and GC. The results demonstrate that healthy tendons presented an average temperature difference of 0.24 ± 0.15 ºC between legs with a maximal difference of 0.4 ºC. On the other hand, unilateral tendinopathy presented an average temperature difference of 1.2 ± 0.9 ºC, however, this difference could be as big as 5.1 ºC. Conclusion: It is concluded that infrared thermography can be used safely and non-invasively to aid in the diagnosis of Achilles tendon tendinopathy.